An Introduction to Economic Analysis of Pest Management: A Case Study of Nematode Management - Yi Li; Yetian Cai; Weizhe Weng; Johan DeSaeger; Zhengfei Guan (EDIS)
The economic performance of pest management practices is a critical factor when farmers make adoption decisions. Partial budget analysis is a widely used tool to evaluate the financial effects of different management practices in agricultural production. It provides an economic rationale for selecting the optimal treatment by evaluating the cost-effectiveness of the treatment. This publication explains how to employ partial budget analysis using a real-world example. It provides a step-by-step guide examining the costs and benefits of two different approaches, fumigation and nematicides, to manage nematodes on Florida's tomato farms.